リーセル ラルセン ハントウ ノ シン コウテイペンギン ルッカリー - 星合, 孝男; ホシアイ, タカオ; 中条, 賢治; チュウジョウ, ケンジ; HOSHIAI, Takao; CHUJO, Kenji (国立極地研究所, 1976)
P(論文) 1975年10月1日,第16次越冬隊員4名により,コウテイペンギンのルッカリーが発見された.ルッカリーの所在地はほぼ68゜50'S,34゜40'Eで,リーセル・ラルセン半島の東岸,からめて岬(69°09'S,35°26'E)の北西約47kmの位置であった.この位置はリーセル・ラルセン半島の先端の開水面から25kmほどの所で,摂餌には好都合の位置である.また,ルッカリーは棚氷の真下にあり,東側には氷山列が認められ,斜面下降風と北東からの卓越風とを避けえられる位置にあると考えられる.個体数は10月24日,ひなも含めて約7,200羽であったが,季節を追って減少した.また,11月2日には,ペンギンの群は元の位置から約1km北東に認められた.11月8日には群が3分し,11月29日には2群が認められた.さらに,1976年1月6日には,ペンギンの群は分散し,個体数も1,300羽となっていた. On October 1, 1975, an emperor penguin rookery designated Riiser-Larsen Peninsula rookery was discovered on the sea ice at the position of 68°50'S, 34°40'E, near Karamete Point on the east coast of the Riiser-Larsen Peninsula. Taking aerophotographs of the rookery, six aerial observations were made from October 22, 1975 to January 6, 1976. Population estimated on October 24 was 7,200 including chicks. The colony remained near the rookery site until late October but moved about 1 km NE of the original site by the beginning of November. Population decreased with the lapse of time. By the beginning of January 1976 the population was 1,300 and colonies started to disperse. departmental bulletin paper